Transformation of adaptive and contextual Islamic curriculum from Abdullah Saeed's education perspective - Wahyu Sihab (Universitas Pendidikan Indonesia, 2025)
Islamic education faces various challenges amid global changes that demand a more relevant and adaptive approach. Abdullah Saeed proposes a contextual ijtihad strategy to improve the adaptability and relevance of Islamic education. This article aims to explore Abdullah Saeed's thoughts on Islamic education, particularly in the context of creating a contextualized and flexible curriculum. This research examines the fundamental concepts of Saeed's philosophy and their application to the development of an Islamic curriculum through a literature study approach. The research method employed is a literature review, which involves reviewing relevant journals, articles, books, and official documents. The conclusion of this study reveals that Abdullah Saeed's contextual approach facilitates Islamic education that is more adaptable and relevant to contemporary life. The curriculum based on this approach not only provides a normative understanding but also encourages students to apply Islamic principles critically within their socio-cultural context. This is expected to produce a generation that is responsive to social change and make Islamic education relevant and constructive for modern society. Abstrak Pendidikan Islam menghadapi berbagai tantangan di tengah perubahan global yang menuntut pendekatan yang lebih relevan dan adaptif. Abdullah Saeed mengajukan strategi ijtihad kontekstual untuk meningkatkan kemampuan adaptasi dan relevansi pendidikan Islam. Artikel ini bertujuan untuk mengeksplorasi pemikiran Abdullah Saeed dalam konteks pendidikan Islam, khususnya yang berkaitan dengan pembuatan kurikulum yang kontekstual dan fleksibel. Penelitian ini melihat ide-ide dasar filosofi Saeed dan bagaimana hubungannya dengan penciptaan kurikulum Islam dengan menggunakan pendekatan studi literatur. Metode penelitian yang digunakan adalah studi literatur dengan mengkaji jurnal, artikel, buku, dan dokumen resmi yang relevan. Kesimpulan dari penelitian ini menunjukkan bahwa pendekatan kontekstual Abdullah Saeed memungkinkan pendidikan Islam yang lebih adaptif dan relevan dengan kehidupan modern. Kurikulum yang didasarkan pada pendekatan ini tidak hanya memberikan pemahaman normatif tetapi juga mendorong siswa untuk menerapkan prinsip-prinsip Islam secara kritis sesuai dengan konteks sosial-budaya. Hal ini diharapkan dapat menghasilkan generasi yang tanggap terhadap perubahan sosial dan menjadikan pendidikan Islam relevan dan konstruktif bagi masyarakat modern. Kata Kunci: Abdullah Saeed; pendidikan Islam; rekonstruksi pemikiran